Cutaneous Rhinosporidiosis - Shrivastava Alok; Bhat Daritri; Parate Sanjay; Bobhate S. K (Wolters Kluwer Medknow Publications, 1997)
Rhinosporidiosis, an infection caused by Rhinosporidium seeberi, predominatly causes lesions in nose followed by conjunctiva. Rarely the other mucocutaneous junctions are involved. Cutaneous rhinosporidiosis is infrequent and is associated with adjacent mucocutaneous disease. We present a case of cutaneous rhinosporidiosis which was not associated with disease elsewhere in the body and is very rare.